Progress in the chemistry of organic natural products Vol. 94 - Kinghorn, A. Douglas; Falk Heinz; Kobayashi, Junichi (Fortschritte der Chemie organischer Naturstoffe / Progress in the Chemistry of Organic Natural Products, 2011)
The three reviews cover the advances in the chemistry and biology of withanolides over the last 16 years, review the chemistry and biology of the rocaglamide-type derivatives and related compounds, with emphasis on their structural diversity, biosynthesis, pharmacological significance and total synthesis, and summarize the extensive chemistry and biology studies on a natural product, which have resulted in a novel therapy approved worldwide.